(untitled) (Bangladesh Journal of Zoology, 2022)
A study was carried out to determine dichlorodiphenyltrichloroethane (DDT) and its metabolites in Gangetic mystus, Mystus cavasius and spotted snakehead, Channa punctatus. DDTs was extracted by QuEChERS method, cleaned-up by H2SO4 treatment and analyzed by GC with Electron Capture Detector. The calibration curves were linear over the range of the tested concentrations as shown by the fact that the correlation coefficients (r2) for the linearity range were 0.995-0.999. The detection limit was found to be 5ppb for DDTs and the quantification limit was 6.5ppb. Recoveries were found (70-130%); this is acceptable for fish samples according to standard methodology. The DDT and its metabolites were not detected in the liver of M. cavasius and C. punctatus. In this study, M. cavasius was found to contain detectable amount of residual targeted pesticides DDTs at 64.21 ppb in digestive tract, 75.23 ppb in gill, 119.82 ppb in gonad and 45.84 ppb in muscle. The C. punctatus residual targeted DDTs were at 8.42 ppb in digestive tract, 4.04 ppb in gill, 56.44 ppb in gonad and 23.15 ppb in muscle. However, this study shows the higher DDT and its metabolites were in the gonad of M. cavasius and C. punctatus. Bangladesh J. Zool. 49 (3): 393-402, 2021